2021
DOI: 10.1515/nanoph-2021-0191
|View full text |Cite
|
Sign up to set email alerts
|

Membrane composition is a functional determinant of NIR-activable liposomes in orthotopic head and neck cancer

Abstract: Near-infrared (NIR)-activable liposomes containing photosensitizer (PS)-lipid conjugates are emerging as tunable, high-payload, and tumor-selective platforms for photodynamic therapy (PDT)-based theranostics. To date, the impact that the membrane composition of a NIR-activable liposome (the chemical nature and subsequent conformation of PS-lipid conjugates) has on their in vitro and in vivo functionality has not been fully investigated. While their chemical nature is critical, the resultant physical conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…This is not unexpected, as we have previously shown that liposomes containing phospholipid conjugates of PSs accumulate in endolysosomal compartments both with and without receptor targeting. [14,33,37,38] Immediately following 690 nm photodynamic activation with 40 J cm −2 , the TPMIL constructs destabilized, which progressed for 5 days following irradiation, suggesting irreversible bilayer disruption as a mechanism for phototriggered irinotecan release (Figure S3a,b, Supporting Information). Phototriggered irinotecan release from the TPMIL constructs in 10% FBS solutions at 37 °C was quantified using LC-MS/MS upon 40 J cm −2 photodynamic activation with 690 nm light (Figure S3c-e, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is not unexpected, as we have previously shown that liposomes containing phospholipid conjugates of PSs accumulate in endolysosomal compartments both with and without receptor targeting. [14,33,37,38] Immediately following 690 nm photodynamic activation with 40 J cm −2 , the TPMIL constructs destabilized, which progressed for 5 days following irradiation, suggesting irreversible bilayer disruption as a mechanism for phototriggered irinotecan release (Figure S3a,b, Supporting Information). Phototriggered irinotecan release from the TPMIL constructs in 10% FBS solutions at 37 °C was quantified using LC-MS/MS upon 40 J cm −2 photodynamic activation with 690 nm light (Figure S3c-e, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are also consistent with our prior work where we have shown that phototriggered release of the small molecule inhibitor cabozantinib and the water soluble fluorophore calcein disodium salt using BPD and BPD-PC embedded liposomes is an entirely photochemical process. [14,36,37] The in vitro (photo)therapeutic efficacy of the constructs in MIA PaCa-2 cells is summarized in Table S2, Supporting Information. Results show that without light, the TPMIL construct (IC 50 = 237.07 ± 75.64 nm) provides a 4.9-fold greater degree of cytotoxicity, as compared to the untargeted PMIL construct (IC 50 = 1167.67 ± 256.54 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were cultured in DMEM (Corning) containing 10% Fetal Bovine Serum (R&D Systems). 7.5 x 10 5 FaDu cells suspended in 20 μl sterile 1X DPBS were implanted orthotopically transcervically into the floor of the mouth according to previously published procedures ( 28 , 29 ). 15 d following tumor implantation, the tumors reached a diameter of ca.…”
Section: Methodsmentioning
confidence: 99%